The Correlation between Serum Biomarkers and Electrocardiogram Characteristics, Pulse Wave Velocity, Blood Lipid Levels, and Carotid Atherosclerosis in Patients with Type 2 Diabetes Mellitus: Serum Biomarkers (adiponectin, leptin, sICAM-1, IL-6, FGF-21) , ECG, PWV, and Blood Lipid Levels for Diabetic CAS - Wang, Huixin (Journal of Medical Biochemistry, 2026)
Background: Patients with type 2 diabetes mellitus (T2DM) often suffer from atherosclerosis, and timely stratification of patient risk is crucial for preventing cardiovascular events. Objectives: It aimed to explore the correlation between electrocardiogram (ECG) characteristics, pulse wave velocity (PWV), blood lipid levels, and novel serum biomarkers with carotid atherosclerosis (CAS) in T2DM patients, providing a multidimensional assessment basis for early identification of high-risk patients. Methods: A retrospective study included 201 T2DM patients at Zhongshan Hospital (Xiamen), Fudan University from January 2024 to December 2025. Patients were allocated to control group (AG, 91 cases with normal carotid arteries or only intimal thickening) or observation group (BG, 110 cases with carotid plaques). General data, ECG indicators, vascular function indicators, blood glucose, blood lipid levels, low-sensitivity C-reactive protein (CRP-L), and novel serum biomarkers (adiponectin, leptin, sICAM-1, IL-6, FGF-21) were collected. Results: The BG had significantly longer P wave duration (PR) and corrected QT (QTc)interval, with higher PWV-Left and PWV-Right; Fasting plasma glucose (FPG), triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels were lower, and glycated hemoglobin (HbA1c) and CRP-L were significantly elevated in the BG (P
Keywords: type 2 diabetes mellitus; carotid atherosclerosis; electrocardiogram; pulse wave velocity; blood lipid levels; high-sensitivity C-reactive protein; glycated hemoglobin; novel serum biomarkers; adiponectin; interleukin-6; endothelial dysfunction